1976
DOI: 10.1056/nejm197607222950402
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure of Glomerular Origin during Visceral Abscesses

Abstract: We studied 11 patients who had visceral abscesses and in whom acute renal failure developed. All renal biopsies showed a diffuse proliferative and crescentig glomerulonephritis. In seven patients blood cultures were repeatedly negative. Endocarditis could be ruled out in six patients. Seven patients had circulating cryoglobulins; serum complement levels were normal in seven and decreased in four; circulating immune complexes were found in the three patients studied. The evolution of the glomerulonephritis, doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

1977
1977
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(28 citation statements)
references
References 19 publications
2
24
0
2
Order By: Relevance
“…Thus, the deterioration of renal function was considered to be from the relapse of the superantigen-related glomerulonephritis induced by the continuous MRSAinfection. In addition to the superantigen-related glomerulonephritis, staphylococcal infections associated with glomerulonephritis have been reported: bacteremia associated with infected ventriculoatrial shunt (6), bacteremia associated with endocarditis (7), and glomerular lesion associated with visceral abcesses (8). In these cases, the level of complement is low, cryoglobulins are frequent, and the elevated immunoglobulin type is IgG but not IgA.…”
Section: Case Reportmentioning
confidence: 99%
“…Thus, the deterioration of renal function was considered to be from the relapse of the superantigen-related glomerulonephritis induced by the continuous MRSAinfection. In addition to the superantigen-related glomerulonephritis, staphylococcal infections associated with glomerulonephritis have been reported: bacteremia associated with infected ventriculoatrial shunt (6), bacteremia associated with endocarditis (7), and glomerular lesion associated with visceral abcesses (8). In these cases, the level of complement is low, cryoglobulins are frequent, and the elevated immunoglobulin type is IgG but not IgA.…”
Section: Case Reportmentioning
confidence: 99%
“…The renal disease can occur 5 days to 4 weeks following the staphylococcal infection, and all of these patients have a strong chance for renal recovery under eradication of the underlying infection. 3 In our case, glomerulonephritis developed after the first week of treatment, and recovery of renal function occurred due to successful treatment of osteomyelitis.…”
Section: Discussionmentioning
confidence: 55%
“…The severity of renal insufficiency is proportional to the degree of proliferation and crescent formation. [1][2][3] At least 2 of the following criteria must be present for diagnosis of Staphylococcus-related glomerulonephritis: hypocomplementemia, endocapillary proliferation and exudation glomerulonephritis on light microscopy, and immunoglobulin A (IgA) dominant or codominant glomerular staining on immunofluorescence microscopy and hump-shaped subepithelial deposits on electron microscopy. Treatment of the disease in adults should focus on eradicating the infection, relieving symptoms, and controlling hypertension and edema.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ileal bypass surgical procedure complicated by migratory arthritis, cryoglobulins were detected and found to contain anticolonic bacterial activity; some of the patients also had evidence of complement depletion (2 1). Beaufils et a1 reported that in 7 of 11 cases of visceral abscess associated with renal failure, cryoglobulinemia was present (22). However, the cryoglobulins were not examined for antibacterial activity to the causative organism.…”
Section: Discussionmentioning
confidence: 99%